Биомеханические аспекты экспериментального исследования функционального лечения С-образной сколиотической деформации позвоночника - Головаха, М. Л.; Тяжелов, А. А.; Летучая, Н. П.; Суббота, И. А.; Карпинский, М. Ю.; Головаха, Максим Леонідович; Тяжелов, О. А.; Летуча, Н. П.; Суббота, І. А.; Карпінський, М. Ю.; Golovaha, M. L.; Tiazhelov, O. A.; et al. (Донецкий национальный медицинский университет им. М. Горького, 2019)
Резюме. Актуальность. В нашей клинической практике был разработан комплекс физических упражнений, во главу которого были поставлены топические особенности деформации позвоночника. Цель работы: на основе математического моделирования обосновать эффективность физиофункционального лечения пациентов c C-образной деформацией позвоночника. Материалы и методы. В качестве экспериментального исследования мы использовали математическое моделирование, основой которого являлась математическая модель позвоночника, позволяющая изучить распределение внутренних напряжений в позвоночных двигательных сегментах при различных вариантах их нагружения. На данной математической модели были проверены 15 упражнений. Выводы. Исследование с помощью математической модели позволило изучить дифференцированное воздействие методов кинезитерапии на С-образную деформацию позвоночника в зависимости от ее вершины. Данное исследование позволило биомеханически обосновать показания и противопоказания для использования различных физических упражнений при лечении сколиотической болезни. Проведенное исследование позволило усовершенствовать методологический подход к разработке комплексов лечебной гимнастики с учетом топических особенностей деформации позвоночника. Резюме. Актуальність. У нашій клінічній практиці був розроблений комплекс фізичних вправ, в основу якого були покладені топічні особливості деформації хребта. Мета роботи: на підставі математичного моделювання обґрунтувати ефективність фізіофункціонального лікування пацієнтів із С-подібною деформацією хребта. Матеріали та методи. Як експериментальне дослідження ми використовували математичне моделювання, основою якого була математична модель хребта, що дозволила вивчати розподіл внутрішніх напружень у хребцевих рухових сегментах при різних варіантах навантаження. На даній математичній моделі було перевірено 15 вправ. Висновки. Дослідження за допомогою математичної моделі дозволило вивчити диференційний вплив методів кінезітерапії на С-подібну деформацію хребта при лікуванні сколіотичної хвороби. Дане дослідження дозволило біомеханічно обґрунтувати показання та протипоказання до використання різних фізичних вправ при лікуванні сколіотичної хвороби. Проведене дослідження дозволило удосконалити методологічний підхід до розробки комплексів лікувальної гімнастики з урахуванням топічних особливостей деформації хребта. Abstract. Background. Scoliotic disease is the object of numerous developments and studies of a wide variety of medical specialists. The multifaceted approach to one of the most difficult topics of orthopedics, vertebrology and pediatrics is absolutely justified. The data speak not only of an increase in the incidence of scoliosis as a whole, but also of an increase in the number of patients with severe deformities. Recently, in the treatment of this pathology, a surgical approach to correcting the deformation of the spine produces good results, while patient management actively includes in its program such a powerful factor as functional treatment of patients after surgery and patients who do not undergo surgical intervention. Many different methods of therapeutic gymnastics have been developed, but it is not always possible to evaluate all the proposed complexes subjectively. In our clinical practice, a set of physical exercises was developed, with topical features of the spinal deformity at its head. The purpose was to substantiate the effectiveness of physio-functional treatment of patients with C-shaped scoliotic disease based on mathematical modeling. Materials and methods. In the biomechanics laboratory of Sytenko Institute of Spine and Joint Pathology, mathematical models of the spine with C-shaped scoliotic deformations were developed, they were used to analyze the stress-strain state. We were interested in the distribution of internal stresses in the model, and not in the magnitude of the stresses produced by this force, so in all cases the load was assumed to be 10 N. In cases of additional compensating forces associated with maintaining the trunk in the initial position, for example, in a one-leg standing, additional load equal to 2 N was applied. As an experimental study, we used mathematical modeling, the basis of which was the mathematical model of the spine that made it possible to study the distribution of internal stresses in vertebral motor segments under different loading patterns. In this mathematical model, 15 exercises were tested. Conclusions. The study with the help of a mathematical model allowed studying the differentiated effect of kinesitherapy methods on spinal deformities, depending on its apex. This study allowed biomechanical substantiation of indications and contraindications for the use of various physical exercises in the treatment of scoliotic disease. The study made it possible to improve the methodological approach to the development of therapeutic gymnastics, taking into account the topical features of spine deformity.
Біомеханічні аспекти експериментального дослідження функціонального лікування С-подібної сколіотичної деформації хребта
Biomechanical aspects of experimental study of functional treatment of C-shaped scoliosis
Keywords: сколиоз; экспериментальное моделирование; функциональное лечение; сколіоз; експериментальне моделювання; функціональне лікування; scoliosis; experimental modeling; functional treatment